The Effect of Working Capital Turnover and Current Ratio (CR) on Return on Investment (ROI) at PT Harum Energy, Tbk (A Company Listed on the Indonesia Stock Exchange Period 2015-2022) - Dhea Adhistiany Sopyan; Nia Kurniasari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine the effect of working capital turnover and current ratio (cr) on return on investment (roi) at PT Harum Energy, Tbk for the period 2015-2022. The research method used is a descriptive associative method. The population consists of secondary data from the financial statements of PT Harum Energy, Tbk. The sample taken used non-probability sampling with purpose sampling method with specific criteria, see the quarterly financial reports of PT Harum Energy, Tbk for the period 2015-2022. To test the influence analysis, Pearson product moment correlation analysis, coefficient of determination analysis, multiple linear regression analysis and t-test and F-test hypothesis testing were applied. The results of the investigation demonstrate that the value of the correlation between working capital turnover and (roi) is -0,193 the correlation value of this falls into the extremely low group, current ratio to return on investment is 0,251 It falls under the low group. The outcomes of the determination analysis show that the quantity of the independent variables influence and contribution (working capital turnover and current ratio) to the dependent variable (return on investment) is 25% and the remainder 75% is affected by additional factors that the author did not look into